IMPLEMENTASI METODE 5-GROOVE DALAM SOFTWARE VISUAL GRAFIS SEBAGAI PENUNJANG PROSES KREATIF PEMBUATAN TEATER - Panji Novantara (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2018)
5-Groove is a method created by researchers in combining various software for the creative process of theater making. As is known, the growth of theater in Indonesia, especially the contemporary theater that always combines the application of technology in its application occurs so rapidly. In fact, Indonesian theaters are often performed abroad. This is a challenge for people to be able to create a more unique theater, attracted foreign countries, and can take advantage of existing technology in the making.5-Groove means 5 software paths that can be done for theater creation in sequence. Dramatica Pro is used to create a play of theater performances, ranging from outline, plot, character creation and characterization, physical characteristics of characters, plot, and the whole process of making the whole script. Photoshop CS3 obviously serves as a software for editing images like theater stage background. MatLab is known as a useful application for graphics creation, but actually this software can be used to cut the song format. Wav, so the song only sounds instrumental. In addition, also assisted by the Power Sound Editor. Autodesk 3ds Max is an application for creating an overview in blocking theater as well as the stage property layout, Corel VideoStudio 12.0 is the last application in the theater making process, as it is a video editing software which is used after theater performances are completed.With 5-Groove, making the theater can be simpler because it uses easy-to-reach software, which can reduce production costs and be more economical.